IDENTITY FORMATION IN GIBB’S SWEETNESS IN THE BELLY AND MUKHERJEE’S DESIRABLE DAUGHTERS - Sarvina, Derry (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2017)
Diaspora is a literary work written as a consciousness toward the differences between old and new culture. The issues whose are able to be taken in Diaspora is the alienation problems, the homesick feeling, the past nostalgia, and also the adaptation process effecting toward crisis identity. This fact encourages the writer to conduct a research in relation with the topic of diasporic problems in cultural identity formation. This research is aimed to describe 1) the efforts of main characters in dealing with their identity crisis, 2) the factors that encourage and support main characters in forming their identity, and 3) the similarities and differences of identity formation toward two novels by using Bhabha’s Hibridity theory. Data source of this research was taken from words, phrases, sentences, statements, dialogues and monologues which record the thought and actions of the characters in the novels of Sweetness in the Belly and Desirable Daughters. As result, this research finds out that the novels described clearly the efforts of main characters—Lilly and Tara—in forming their cultural identity as immigrants or diaspora. In the novel Sweetness in the Belly, it is started by Lilly’s efforts in establishing her identity in Harare-Ethiopia and London, how the main character does acceptance and resistance to the culture where she lives, and how the influence of her friends are in finding her identity. While Tara, in Desirable Daughters, it is begun by her understanding on diversity in Advanced country. It is found the binary opposition between herself and her oldest sister in the same country as immigrants, then how her efforts and her sister’s influences in forming her identity. Then, these novels show that there are similarities and differences in determining main characters’ identity through their own experience life. Last, this research finds out that the forming of cultural identity deals with split/ ambivalence. This thing will cause hybridity that is the result of assimilation from two different cultures, East and West.